Nutritional status and body composition of young artistic gymnasts from Bulgaria - Kolimechkov, S.; Yanev, I.; Kiuchukov, I.; Petrov, L.; Alexandrova, A.; Zaykova, D.; Stoimenov, E. (Journal of Applied Sports Sciences, 2019)
Young gymnasts should not have excessive body mass because that might lead to under-performance. Therefore, children practising gymnastics should consume a balanced diet, which will promote their physical abilities and optimal body mass. The aim of this study was to compare the nutrient intake of young Bulgarian artistic gymnasts to matched groups from the National Nutrition Survey in Bulgaria (NNSB2003). The study consisted of 76 artistic gymnasts (5 to 14 years of age) from four cities in Bulgaria, and the participants were divided into three groups in accordance with the age and gender categories applied in the NNSB2003. Anthropometric measurements were taken and a food frequency questionnaire was applied in order to assess the body composition and nutrient intake of the gymnasts. The percentile scores in the height and %Fat of the gymnasts were significantly lower than the 50th percentile of the international norms. The energy intake of the gymnasts did not differ significantly from those reported in the NNSB2003, whilst the protein intake, relative protein intake, and energy contribution of proteins were significantly higher than those in the same survey. The energy contribution of fats was above the recommended norms (15-30%), as provided by the WHO. The fat intake was slightly higher, and the carbohydrate intake was slightly lower than the recommended values in the literature, and, therefore, the former should be reduced and the latter increased in their food.Key words: nutrition, diet, body composition, artistic